Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Fisik Terhadap Kinerja Pegawai Pada Kantor Dinas Pendidikan Tuapejat Kabupaten Kepulauan Mentawai - -, Helentina - (Pendidikan Ekonomi, 2014)
This research on the background of the background by the Environmental Effects of Leadership Style and Physical Work Performance Against Employees In Education Office Mentawai Islands, the type of research is descriptive and verification methods, research was conducted at the District Education Office Mentawai Islands. The population in the study were all employees of the Mentawai Islands Department of Education totaling 49 employees. The sampling technique using census method ie the number of samples is the entire population so that the sample was obtained by 49 respondents. Instrument research using questionnaires and documentation. While the analysis of the data used is multiple linear regression. From the analysis of the data showed that a significant effect of leadership style on employee performance where tcount of 5.828> 1.657 with significant ttable 0.000 <0.05. There is significant influence of the physical work environment on employee performance where tcount for 2,993> ttable of 1.657 with significant value of 0.004 <0.05. There is significant influence between leadership style and the physical work environment on employee performance in which the value of F at 22 553> Ftable of 3.07 with significant value 0.000 <0.05. Based on these results we can conclude that the leadership style and physical work environment are two factors that can influence the performance of employees in the Mentawai Islands District Education Office. Thus it is suggested to the head of the Mentawai islands in order to focus on factors increase employee performance, and encouraging or uplifting in a way paying attention and a comfortable environment in order to improve the performance better.